MANAGEMENT AND MARKETING STRATEGY OF PEMPEK MANG PARI 19 ILIR - , HENDRA RIDHO M ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Graduating Paper aims to explain about the short profile of Pempek Mang Pari 19 Ilir restaurant, also it tells about the history about Pempek Mang Pari restaurant, in addition it contains with the making process of pempek and cuko in Pempek Mang Pari restaurant. Next, this graduating paper contains about the management and marketing system that used in Pempek Mang Pari restaurant. In order to achieve the goal and profit, the marketing strategy are needed in a company to organize the entire activities inside it. In this research the writer uses the â4 Pâsâ theory, where the âPâ letter is a formula to implementing the marketing system. Each of 4 P consist of: Product, Price, Place and Promotion. The methods of collecting data in this research are direct observation, interview, and library research. Direct observation is conducted for one month to identify the management and marketing system inside the restaurant of pempek Mang Pari 19 Ilir. Interview purposes to get the information which are needed to this research. And the library research is done to collect the additional information that related with the research to support the discussion of this graduating paper. Besides, the writer spreads the questionnaire to the customer of Pempek Mang Pari restaurant. Based on the customerâs opinion, the writer analyses and turns it into data as the strengthening facts of the research.